2015
DOI: 10.1007/s10620-015-3697-6
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Repeat Endoscopy in Barrett’s Esophagus with No Dysplasia and Low-Grade Dysplasia: A Population-Based Study

Abstract: Background The yield of early repeat endoscopy in patients with Barrett’s esophagus (BE) is not well established. Aims To determine how often early repeat endoscopy detected missed dysplasia or esophageal adenocarcinoma (EAC) in a population-based cohort of patients with BE. Secondary aims were to identify risk factors for missed dysplasia/EAC, and compare detection of prevalent versus incident HGD/EAC. Methods A population-based cohort of BE subjects in Olmsted County, MN was studied. Patients with initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
(37 reference statements)
0
24
1
Order By: Relevance
“…8,9 Furthermore, as most cancer screening tools have a miss rate, one can speculate that there might be cancers that are missed at the index endoscopy during which an initial BE diagnosis is made. Indeed, in recent large population-based studies with long-term follow-up, 58%–66% of EACs detected were diagnosed within 1 year of index endoscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Furthermore, as most cancer screening tools have a miss rate, one can speculate that there might be cancers that are missed at the index endoscopy during which an initial BE diagnosis is made. Indeed, in recent large population-based studies with long-term follow-up, 58%–66% of EACs detected were diagnosed within 1 year of index endoscopy.…”
mentioning
confidence: 99%
“…2,3 Using data from the Olmsted County population-based cohort of BE patients, we observed that 2% of patients might have missed HGD or EAC and 10% have missed dysplasia when endoscopy is repeated in 1–2 years. 9 As a result, one has to question whether the missed EAC group is an important BE population to target for detection of dysplasia via methods, such as a 1-year follow-up endoscopy, which currently is not recommended by any of the 3 major gastroenterologic societies. 1012 …”
mentioning
confidence: 99%
“…Th e rate can decrease if, over time, there is a decrease in environmental insult (such as acid refl ux) and/or if metaplastic mutations tend to stabilize over time. In addition, multiple negative endoscopies may improve the negative predictive value of endoscopy and hence identify a low risk group (missed rate of dysplasia at index endoscopy=9.5%) ( 34 ). On the contrary, the rate can increase if environmental noxious stimuli continue unabated or due to increase in probability of mutations by sheer number of mitotic cycles over time.…”
Section: Is Persistence Of Ndbe Protective Against Progression To Eac?mentioning
confidence: 99%
“…No randomized, controlled trials have supported decreased mortality as a result of these programs, but given evidence from cohort and retrospective studies combined with the rapidly rising incidence of esophageal adenocarcinoma (EAC), some GI societies have weakly recommended screening and surveillance endoscopy for BE patients [1]. The goal of the initial endoscopy is to detect BE and, if detected, to grade and evaluate for the presence of dysplasia and EAC.In this issue of Digestive Diseases and Sciences, Visrodia et al [2] report the proportion of cases of ''missed dysplasia'' diagnosed at repeat endoscopy in comparison with the index endoscopy findings. In this retrospective study, patients who underwent initial endoscopy from 1976 to 2011, with diagnosed BE of length 1 cm or greater, i.e., columnar mucosa with intestinal metaplasia, and who had undergone repeat endoscopy within 24 months of the index examination, were included in the analysis.…”
mentioning
confidence: 99%
“…In this issue of Digestive Diseases and Sciences, Visrodia et al [2] report the proportion of cases of ''missed dysplasia'' diagnosed at repeat endoscopy in comparison with the index endoscopy findings. In this retrospective study, patients who underwent initial endoscopy from 1976 to 2011, with diagnosed BE of length 1 cm or greater, i.e., columnar mucosa with intestinal metaplasia, and who had undergone repeat endoscopy within 24 months of the index examination, were included in the analysis.…”
mentioning
confidence: 99%